Nascent transcript analysis of glucocorticoid crosstalk with TNF defines primary and cooperative inflammatory repression - Sasse, Sarah K. (Genome Res, 2019)
The glucocorticoid receptor (NR3C1, also known as GR) binds to specific DNA sequences and directly induces transcription of anti-inflammatory genes that contribute to cytokine repression, frequently in cooperation with NF-kB. Whether inflammatory repression also occurs through local interactions between GR and inflammatory gene regulatory elements has been controversial. Here, using global run-on sequencing (GRO-seq) in human airway epithelial cells, we show that glucocorticoid signaling represses transcription within 10 min. Many repressed regulatory regions reside within “hyper-ChIPable” genomic regions that are subject to dynamic, yet nonspecific, interactions with some antibodies. When this artifact was accounted for, we determined that transcriptional repression does not require local GR occupancy. Instead, widespread transcriptional induction through canonical GR binding sites is associated with reciprocal repression of distal TNF-regulated enhancers through a chromatin-dependent process, as evidenced by chromatin accessibility and motif displacement analysis. Simultaneously, transcriptional induction of key anti-inflammatory effectors is decoupled from primary repression through cooperation between GR and NF-kB at a subset of regulatory regions. Thus, glucocorticoids exert bimodal restraints on inflammation characterized by rapid primary transcriptional repression without local GR occupancy and secondary anti-inflammatory effects resulting from transcriptional cooperation between GR and NF-kB.